Changes in colonic microbiotas in rat after long-term exposure to low dose of okadaic acid. (September 2020) - Liu, Yang; Zheng, Jian-Wei; Peng, Xi-Chun; Li, Hong-Ye; Huang, Lu; Li, Da-Wei; Liu, Jie-Sheng; Yang, Wei-Dong
Abstract: Okadaic acid (OA), one of the most important phycotoxins, is widely distributed around the world, concerning diarrheic shellfish poisoning (DSP), and even colorectal cancer. Here, we found that long-term exposure of OA at a low dose (80 μg kg −1 body weight) had certain effects on colonic microbiotas and tract in rat. In the OA-exposed rat, colonic epithelium layer was damaged, and relative abundance of some microbiotas were significantly changed, especially genera in Clostridiales. However, no intestinal inflammation or significant disease was observed. Combined with the increase in relative abundance of some genera in Clostridiales induced by OA in the fermentation experiment, we proposed that OA could cause damage to the intestinal epithelium and increase the relative abundance of pathogenic bacteria, thereby increasing the probability of contact between intestinal epithelium and pathogenic bacteria and leading to an easier pathogenicity. Graphical abstract: Image 1 Highlights: OA in low dose could disturb the gut microbiotas in rat. OA exposure could lead damage to the epithelium, but not liver in rat. Our finding might give a valuable insight into the harm of OA on public health.